2016
DOI: 10.1016/j.neuroimage.2015.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Contingent negative variation (CNV) associated with sensorimotor timing error correction

Abstract: Introduction: Detection and subsequent correction of sensorimotor timing errors is fundamental to adaptive behavior. Using scalp-recorded event-related potentials (ERPs), we sought to find ERP components that are predictive of error correction performance during rhythmic movements.Method: Healthy right-handed participants were asked to synchronize their finger taps to a regular tone sequence (every 600 ms), whilst EEG data were continuously recorded. Data from 15 participants were analyzed. Occasional irregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
4
14
0
Order By: Relevance
“…By inducing perturbations and errors in SMS, we can gain insight into the underlying timing mechanisms. A common method to induce errors in a SMS task is to occasionally perturb an otherwise isochronous metronome (Repp, 2000 , 2001a , b ; Praamstra et al, 2003 ; Repp and Keller, 2004 ; Jang et al, 2016 ; Jantzen et al, 2018 ). Error correction in SMS can be broken down into two distinct mechanisms: a phase-correction mechanism for correcting errors in relative phase, and a period-correction mechanism that corrects changes to the internal timekeeper period (Repp, 2001b ; Repp and Keller, 2004 ).…”
Section: Role Of Error Correction In Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…By inducing perturbations and errors in SMS, we can gain insight into the underlying timing mechanisms. A common method to induce errors in a SMS task is to occasionally perturb an otherwise isochronous metronome (Repp, 2000 , 2001a , b ; Praamstra et al, 2003 ; Repp and Keller, 2004 ; Jang et al, 2016 ; Jantzen et al, 2018 ). Error correction in SMS can be broken down into two distinct mechanisms: a phase-correction mechanism for correcting errors in relative phase, and a period-correction mechanism that corrects changes to the internal timekeeper period (Repp, 2001b ; Repp and Keller, 2004 ).…”
Section: Role Of Error Correction In Timingmentioning
confidence: 99%
“…The neural correlates of error correction reveal more evidence for multiple interacting and overlapping timing mechanisms. Error detection of timing perturbations in auditory SMS tasks modulates the P1, N1, and N2 auditory ERP components depending on both the size and direction of the perturbation (Praamstra et al, 2003 ; Jang et al, 2016 ). Jantzen et al ( 2018 ) also found a theta response stemming from the Pre-SMA and anterior cingulate for error detection, an increase in theta coupling between the SMA and the motor cortex for late perturbations.…”
Section: Underlying Physiology Of the Auditory And Visual Timing Systmentioning
confidence: 99%
“…The CNV is a slow buildup of a negative-going EEG potential during the interval between a warning/cue stimulus (S1) and a target stimulus (S2), which has been interpreted as reflecting the deployment of attention (Babiloni et al, 2003;Bickel et al, 2012;Hamano et al, 1997;Tecce, 1972), timing processes (e.g. gauging expected duration of cue-target interval; Jang et al, 2016;Macar and Vidal, 2009;Mento, 2013;van Rijn et al, 2011) or changes in alertness (Pauletti et al, 2014;Posner, 2008). The CNV is commonly observed over frontal-central regions prior to the delivery of auditory or tactile stimuli (Chennu et al, 2013;Kononowicz and Penney, 2016;Pauletti et al, 2014), and has a strong parietal-occipital distribution preceding visual targets (Gomez, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies of finger tapping have contributed to our understanding of how movement trajectories contribute to error correction in motor timing (Balasubramaniam et al, 2004;Hove et al, 2014). Recently, neuroimaging techniques have also been used to build understanding of the neural basis of error correction in sensorimotor synchronization (SMS) using EEG (Praamstra et al, 2003;Jang et al, 2016) By studying the neural processes involved in visual and auditory SMS, the two modalities can be compared, and thus tested to see to what extent the neural mechanisms of SMS are modality specific or generalized.…”
Section: Introductionmentioning
confidence: 99%